WAKAF HAK ATAS KEKAYAAN INTELEKTUAL DALAM TINJAUAN HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF: (Studi Kasus Pasal 16 ayat 3 Huruf E Hak Atas Kekayaan Intelektual) - Syafi'ie, Imam; Ma'u, Dahlia Haliah; Ardiansyah, Ardiansyah (Al-Usroh, 2024)
This research explains waqf for intellectual property and reviews of Islamic law. As well as answering and knowing: 1) the position of intellectual property rights as an object of waqf in the concept of Islamic law. 2) implementation of the endowment of intellectual property rights if the wakif dies. The position of intellectual property rights as an object of waqf is explained in the Case Study of Article 16 paragraph 3 Letter E of Law Number 41 of 2004 concerning Waqf, as well as the Islamic religious perspective. This research is included in the descriptive qualitative research cluster using a library research approach (literature study), a way of collecting data in research by collecting literary sources such as books that explain waqf, journals related to research, and books that discuss waqf. intellectual property rights, the method of validating data from this research uses four criteria, namely reliability, transferability, reliability and verifiability, and data analysis techniques with data reduction, data display, and data withdrawal. This research shows that: 1) the position of Intellectual Property Rights in Islamic law. The position of intellectual waqf property rights when they become the object of waqf. There are many opinions about this, but in essence, all of them allow or are legal in waqf rights. Even though IPR waqf is basically rarely done, it is permitted by all Islamic schools of thought. Waqf that does not materialize, such as art or the identity of an item, is legally waqf, and the terms return to the basic law of waqf. 2) Implementation of the endowment of Intellectual Property Rights when the person providing the endowment dies. The position of giving IPR is if the waqf is issued before death, then the gift is continued based on the deed, because the gift is a legal act of waqf to separate/transfer part of one's property rights to be used according to the rights and values ??of worship of both the living and the dead. The reward is then received by the reward waqif, so that the reward continues and the waqf remains valid in religious law and in the context of the state.